2014
DOI: 10.1016/j.envint.2014.08.008
|View full text |Cite
|
Sign up to set email alerts
|

EPA's SHEDS-multimedia model: Children's cumulative pyrethroid exposure estimates and evaluation against NHANES biomarker data

Abstract: The U.S. EPA's SHEDS-Multimedia model was applied to enhance the understanding of children's exposures and doses to multiple pyrethroid pesticides, including major contributing chemicals and pathways. This paper presents combined dietary and residential exposure estimates and cumulative doses for seven commonly used pyrethroids, and comparisons of model evaluation results with NHANES biomarker data for 3-PBA and DCCA metabolites. Model input distributions were fit to publicly available pesticide usage survey d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(12 citation statements)
references
References 20 publications
0
11
0
Order By: Relevance
“…This is likely due to the increased use of pyrethroid insecticides in residential settings and some agricultural settings (Barr et al, 2010). Research suggests that mainly permethrin and cypermethrin contributed to the majority of the observed urinary 3-PBA levels in the US general population in the last decade (Morgan, 2012;Xue et al, 2014). A comparison of the available published studies that have reported the median 2,4-D, TCP, 3-PBA, and/or PCP levels (ng/mL) in the urine of the general adult population worldwide are presented in Table 4.…”
Section: Discussionmentioning
confidence: 98%
“…This is likely due to the increased use of pyrethroid insecticides in residential settings and some agricultural settings (Barr et al, 2010). Research suggests that mainly permethrin and cypermethrin contributed to the majority of the observed urinary 3-PBA levels in the US general population in the last decade (Morgan, 2012;Xue et al, 2014). A comparison of the available published studies that have reported the median 2,4-D, TCP, 3-PBA, and/or PCP levels (ng/mL) in the urine of the general adult population worldwide are presented in Table 4.…”
Section: Discussionmentioning
confidence: 98%
“…The trend that dietary ingestion is the major route of insecticide exposure most of the time until non-dietary ingestion becomes significant at the higher percentiles is in support of the work of Xue et al [ 25 ], which used EPA’s SHEDS-multimedia model to estimate pyrethroid intakes for 3–5 years old. They estimated the doses for the general population and specifically for people with pyrethroid use in the homes (i.e., residential use population), and found that exposure via non-dietary ingestion prevailed over that via dietary ingestion above the 95th and 75th percentiles for the general population and residential use population, respectively.…”
Section: Discussionmentioning
confidence: 57%
“…The trend that dietary ingestion is the major route of insecticide exposure with non-dietary ingestion catching up at the high percentiles is in support of the work of Xue et al [26], which used EPA's SHEDS-multimedia model to estimate pyrethroid intakes for 3 -5 years old. They estimated the doses for the general population and specifically for people with pyrethroid use in the homes (i.e., residential use population), and found that exposure via non-dietary ingestion prevailed over that via dietary ingestion above the 95 th and 75 th percentiles for the general population and residential use population, respectively.…”
Section: Discussionmentioning
confidence: 60%